The effect of advertisements and discounts on the interest in staying in dusun bambu during the covid-19 pandemic - Muhammad Rifki Adriadi; Fitri Lestari (Marketing Management Studies, 2023)
This study aims to determine the effect of advertising and discounts on interest in staying at Dusun Bambu Outdoor Dining Resort. The method used is descriptive method. The sampling technique used is probability sampling technique. The type of data in this study is primary in the form of consumer responses through questionnaires regarding variables Advertising and Discounts on Interest in Staying at Dusun Bambu Outdoor Dining Resort. The data analysis used in this study was multiple linear regression at a significance level of 5%. The software used to analyze the data was SPSS 26. The results of this study indicate that advertising and discounts have a positive and significant effect on interest in staying. Interest in staying is influenced by advertisements and discounts of 47.2%.